Comparative efficacy and tolerability of pharmacological interventions for acute bipolar depression in adults: a systematic review and network meta-analysis - Yildiz, Ayşegül; Siafis, Spyridon; Mavridis, Dimitris; Vieta, Eduard; Leucht, Stefan (The Lancet. Psychiatry, 2023)
Bipolar depression constitutes a major public health problem due to its substantial burden of disease. Although pharmacological interventions are available, guidelines required updated evidence synthesis to improve their current recommendations. In order to inform evidence-based prescribing, we investigated the comparative efficacy and tolerability of pharmacological interventions for acute bipolar depression. We conducted a systematic review and network meta-analysis. We searched for randomised controlled trials comparing pharmacological interventions with each other or placebo in adults with acute bipolar depression (type I, type II, or not otherwise specified), excluding those with substance misuse, unipolar depression, or schizophrenia, in MEDLINE, Embase, PsycINFO, Google Scholar, Cochrane Library, Web of Knowledge, CINAHL, and LILACS from database inception up to April 13, 2023. Criteria for eligibility were a duration of 2-16 weeks with masked outcome assessments, and we included combination, add-on design, and monotherapy studies. The co-primary outcomes were depressive symptoms, examined with standardised mean differences (SMDs), and manic switch, examined with odds ratios (ORs). We also investigated dropouts due to any reason, inefficacy, adverse events, and important side-effects as secondary outcomes. The confidence in the evidence was evaluated using Confidence-In-Network-Meta-Analysis (CINeMA). The study was registered with PROSPERO, CRD42020171726. We analysed data from 101 randomised controlled trials covering 20 081 participants, 8063 men (41·7%) and 11 263 women (58·3%; sex not available in four studies), mean age 41·0 years (range of means 28·7-53·6 years), and 68 medications and placebo. Ethnicity data were not available. With moderate confidence in the evidence, olanzapine plus fluoxetine, quetiapine, olanzapine, lurasidone, lumateperone, cariprazine, and lamotrigine were more efficacious than placebo in reducing depressive symptoms, with SMDs ranging from 0·41 (95% CI 0·19-0·64) for olanzapine plus fluoxetine to 0·16 (0·03-0·29) for lamotrigine. Several other drugs might also be efficacious, but the confidence in the evidence was very low to low. Antidepressants as a class seem to be efficacious, but had a higher risk for manic switch compared to antipsychotics. Medications differed in their side-effect profiles. This is, to our knowledge, the largest network meta-analysis of pharmacotherapy for bipolar depression to date. Olanzapine plus fluoxetine, quetiapine, olanzapine, lurasidone, lumateperone, cariprazine, and lamotrigine were found to be more efficacious than placebo in adults with acute bipolar depression, with good confidence in the evidence, and to differ in their side-effect profiles. These findings can inform evidence-based care and the development of treatment guidelines internationally. None.